Exploring the Macroscopic and Microscopic Characteristics of Acalypha indica L. Simplisia Powder in the Context of Pharmabotanical Studies - Saristiana, Yuneka; Anita Dwi Setyarini; Yunita Dian Permatasari; Hasriyani; Arikha Ayu Susilowati; Fendy Prasetyawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Botanical studies form a cornerstone in pharmacy, providing insights into the therapeutic potential of medicinal plants. Acalypha indica L., commonly known as